AN APPLICATION DESIGN IOT WATER STORAGE EQUIPMENT CONTROL SYSTEMS - Mhd Zakki Fatahillah; Pristisal Wibowo; Muhammad Fahreza (Sean Institute, 2023)
This paper focuses on addressing the challenge of monitoring water reservoirs located at high altitudes where direct inspection of water conditions is difficult. To tackle this issue, the research employs a system for real-time control and monitoring. Specifically, the system utilizes a waterflow sensor to measure water flow, an ultrasonic sensor to determine water levels, and a TDS sensor to detect water turbidity. These sensors are connected to an Arduino Atmega 2560. The control logic for filling the reservoir with water is implemented using the Mamdani type fuzzy logic method, which incorporates rules based on water level readings. Moreover, the study integrates IoT (Internet of Things) technology to enable remote monitoring of water levels and turbidity via smartphones. The study's results demonstrate that IoT technology greatly facilitates real-time remote monitoring of reservoir conditions. The trial data indicate an impressive 97% success rate in controlling the water filling process, with an average error of less than 15%. This successful approach can be applied effectively to create a smart home water reservoir control and monitoring system.